Establishing consensus on nutrition competencies for medicine: a Delphi study - Sumantra Ray; Breanna Lepre; Kylie J Mansfield; Eleanor J Beck (BMJ Nutrition, Prevention & Health)
Background Significant research, regulatory bodies and even governmental resolutions have identified meaningful nutrition education for medical and other healthcare professionals as a priority. Doctors are well placed to provide nutrition care, yet nutrition education in medicine remains inadequate regardless of country, setting, or year of training. There remains a need to establish an accepted benchmark on nutrition competencies for medicine, as without consensus standards there is little likelihood of uniform adoption.Objective This study aimed to establish consensus on nutrition competencies using a Delphi process to inform a framework for nutrition education in medicine.Methods A three-round modified online Delphi survey of experts in healthcare practice, education and training, and experts by experience (service users) was conducted to provide a comprehensive consensus on nutrition competencies for medical practice.Results Fifty-two experts (15.1% response rate) participated in Round 1, 42 completed Round 2 and 47 completed Round 3. Participants included medical professionals, dietitians, academics working in health professions education and policymakers from Australia, New Zealand, the UK and Northern Ireland. Twenty-seven service users (57.5% response rate) completed the Round 1 questionnaire, 19 completed Round 2 and 16 completed Round 3. By consensus, 25 nutrition competencies for medicine were defined. The service user panel identified an additional seven skills and attributes considered important in the receipt of nutrition care. Competencies that achieved consensus broadly fell into themes of team-based care, communication, professionalism (eg, attributes) and health promotion and disease prevention. This informs broad skills that may be taught in a nutrition context but could be included in other domains.Conclusions The findings suggest doctors need the knowledge and skills to consider the findings from nutrition screening and assessment, coordinate nutrition care when an individual may benefit from further assessment or intervention and provide support for advice delivered by other experts as part of a multidisciplinary approach.